Structural Equation Modeling in E-Commerce Application Users: Case Study of Shopee - Ronny H. Walean; Douglass Rasuh; Cliford R. Ratulangi (CogITo Smart Journal, 2024)
In line with current developments, especially advances in technology that are increasingly advancing, it facilitates all community activities in buying and selling goods, with the existence of e-commerce now people no longer need to go directly to the store to make these transactions. One of the e-commerce applications that are widely used today is a platform for shopping on the internet called Shopee which is easy to use. This study aims to see what factors are included in the form of acceptance by users of e-commerce applications, especially at Shopee, using Davis' (1989) Technology Acceptance Model (TAM) methodology. In this study, the analysis was conducted on 220 respondents who often or have used the Shopee application using the SEM PLS data analysis tool and a quantitative approach with the SmartPLS application. The results demonstrate the pathway through which users' attitudes toward usage are shaped by their perceptions of usefulness and ease of use, subsequently influencing their behavioral intentions, and ultimately impacting their actual usage behavior on the e-commerce application, namely Shopee. This study comprehensively elucidates the interrelationship among each Technology Acceptance Model (TAM) variable examined. Overall, the application of TAM in investigating the use of Shopee is validated through the findings of this study